Do FLAIR Vascular Hyperintensities beyond the DWI Lesion Represent the Ischemic Penumbra? - Legrand, L.; Tisserand, M.; Turc, G.; Naggara, O.; Edjlali, M.; Mellerio, C.; Mas, J.-L.; Méder, J.-F.; Baron, J.-C.; Oppenheim, C. (American Journal of Neuroradiology, 2015)
BACKGROUND AND PURPOSE: In acute stroke with proximal artery occlusion, FLAIR vascular hyperintensities observed beyond the boundaries of the cortical lesion on DWI (newly defined “FLAIR vascular hyperintensity–DWI mismatch”) may be a marker of tissue at risk of infarction. Our aim was to compare the occurrence of FLAIR vascular hyperintensity–DWI mismatch relative to that of perfusion-weighted imaging–DWI mismatch in patients with proximal MCA occlusion before IV thrombolysis. MATERIALS AND METHODS: In 141 consecutive patients with proximal MCA occlusion, 2 independent observers analyzed FLAIR images for the presence of FLAIR vascular hyperintensity–DWI mismatch before IV thrombolysis. PWI-DWI mismatch was defined as Volumehypoperfusion > 1.8 × VolumeDWI, with Volumehypoperfusion > 6 seconds on time to maximum value of the residue function maps in the 94 patients with available PWI. The presence of FLAIR vascular hyperintensity–DWI mismatch, PWI-DWI mismatch, and infarct growth on 24-hour follow-up DWI was compared. RESULTS: A FLAIR vascular hyperintensity–DWI mismatch was present in 102/141 (72%) patients, with an excellent interobserver reliability (κ = 0.91), and a PWI-DWI mismatch, in 61 of the 94 (65%) patients with available PWI. FLAIR vascular hyperintensity–DWI mismatch predicted PWI-DWI mismatch with a sensitivity of 92% (95% CI, 85%–99%) and a specificity of 64% (95% CI, 47%–80%). Patients with FLAIR vascular hyperintensity–DWI mismatch had smaller initial DWI lesion and larger infarct growth (P < .001) than patients without FLAIR vascular hyperintensity–DWI mismatch, even though their final infarcts remained smaller (P < .001). CONCLUSIONS: Albeit being moderately specific, probably due to inclusion of oligemic tissue, the FLAIR vascular hyperintensity–DWI mismatch identifies large PWI-DWI mismatch with high sensitivity. DWI1pretreatment lesions on DWIDWI2follow-up lesions on DWIFVHFLAIR vascular hyperintensityTmaxtime to maximum value of the residue function